2021
DOI: 10.7860/jcdr/2021/47913.14774
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio in Adult-Onset Still Disease, their Relationship with Baseline Disease Activity and Subsequent Disease Course: A Single-Center Retrospective Cohort Study

Abstract: Introduction: Adult-onset Still Disease (AoSD) is a rare systemic polygenic nonfamilial autoinflammatory disease of unknown aetiology. The long-term course of the disease can be categorised in three different definitions including self-limited course, intermittent course or chronic course. Recently, Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) were investigated in various rheumatic diseases as an informative markers in evaluating severity of inflammation and disease activity. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…They also noted significantly higher NLR and CRP values in active than inactive disease. [ 55 ] A prospective multicenter study noted NLR ≥4 in majority of the AoSD patients with high sensitivity and specificity. Based on which, the authors found its inclusion as a major criterion improving the sensitivity and accuracy of the Yamaguchi and Fautrel classification systems.…”
Section: Introductionmentioning
confidence: 99%
“…They also noted significantly higher NLR and CRP values in active than inactive disease. [ 55 ] A prospective multicenter study noted NLR ≥4 in majority of the AoSD patients with high sensitivity and specificity. Based on which, the authors found its inclusion as a major criterion improving the sensitivity and accuracy of the Yamaguchi and Fautrel classification systems.…”
Section: Introductionmentioning
confidence: 99%
“…After a search of the databases, screening of results, and review of reference lists and citations, a total of five studies met selection criteria 1,[6][7][8][9] (see Table 1). The studies were conducted in China (four studies) 1,6,7,9 and Turkey (one 8 . The studies included data on 412 AOSD patients, with sample sizes varying between 61 and 110 subjects.…”
mentioning
confidence: 99%
“…The studies included data on 412 AOSD patients, with sample sizes varying between 61 and 110 subjects. The control populations included 337 patients with clinical features resembling AOSD, including sepsis (3 studies) 1 , 6 , 7 , fibromyalgia syndrome (1 study) 8 , and fever of unknown origin (1 study) 9 . A total of 157 healthy control subjects were included in two studies 7 , 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation